Commentary: The Judiciary And Sustainable Development: Perspectives Of A Brazilian Federal Judge - Wedy, Gabriel (Journal of Sustainable Development Law and Policy, 2025)
The approval of 17 goals and 169 targets for sustainable development by the United Nations Conference on Post-2015 Development Agenda is unquestionably an advancement for humanity. Economic development alone is however unsatisfactory: it must be paired with human development, respect for the environment and sound governance. Drawing from litigation and jurisprudential development from the Brazilian judiciary, this short legal commentary evaluates the role of the judiciary in promoting sustainable development, especially the attainment of the United Nations Sustainable Development Goals (SDGs).